Modeling fluctuations in the global demand for commodities - Lutz Kilian; Xiaoqing Zhou (Bank of Canada, 2018)
It is widely understood that the real price of globally traded commodities is determined by the forces of demand and supply. One of the main determinants of the real price of commodities is shifts in the demand for commodities associated with unexpected fluctuations in global real economic activity. There have been numerous proposals for quantifying global real economic activity. We discuss which criteria a measure of global real activity must satisfy to be useful for modeling industrial commodity prices, we examine which of the many alternative measures in the literature are most suitable for applied work, and we explain why some popular measures are inappropriate for modeling commodity prices. Given these insights, we re-examine in detail whether global real economic activity has declined since 2011 and by how much. Drawing on a range of new evidence, we show that the global commodity price boom of the 2000s appears to have been largely transitory. Our analysis has important implications for the design of structural models of commodity markets, for the analysis of the transmission of commodity price shocks to commodity-importing and -exporting economies, and for commodity price forecasting.
Keywords: F44; Q11; Q31; Q41; Q43; 330; Econometric and statistical methods; International topics